Actuators and Sensors Based on Tensegrity D-bar Structures - Boz, Utku; Goyal, Raman; Skelton, Robert E. (Frontiers in Astronomy and Space Sciences, 2018)
Tensegrity offers lightweight deployable structures for use in many engineering disciplines. Among all of the available tensegrity forms, D-Bar has a potential for combined applications of sensing, actuation, and structural support. In this paper, we enhance the minimal mass formulation of the D-Bar by including yielding of the compressive members as a design constraint in contrast to the previous assumption which considers buckling as the sole failure mechanism. In addition, we analyze the length and force gains of a D-bar system analytically by considering the minimal mass D-bar as the design constraint. Furthermore, we calculate the stiffness of the D-Bar and when appropriate use as design constraints as well. To enhance the minimal mass properties of the D-Bar, we combine T-bar and D-bar systems. The analysis shows that these structures are the basis for effective force transducers, force-controlled actuators, and efficient deployable compressive structures.